Medical residents’ knowledge, attitudes and practices regarding antibiotics, antimicrobial stewardship and multidrug-resistant bacteria: a cross-sectional study in a major university in Iran - Kiani, Fatemeh; Sajadi, Ghazaleh; Motamedi, Narges; Salmasi, Mehrzad; Solgi, Hamid (Frontiers in Medicine, 2024)
Background: Antimicrobial resistance (AMR) is one of the biggest threats to global public health systems. This study aimed to assess the knowledge, attitudes and practice about AMR, antimicrobial stewardship programs (ASPs) and multidrug-resistant (MDR) bacteria.: A web-based questionnaire survey was conducted among the residents of Isfahan University of Medical Sciences from May to November 2023. Data analysis was done using SPSS version 24.0 software. Results: Overall, 400 out of 450 medical residents responded to the questionnaire, giving a response rate of 88.9%. The participants' ages ranged from 26 to 54 years, and the majority were female (227/400 56.8%). Average scores for knowledge, attitudes, and practices were 53.70±15.88, 36.97±5.89 and 24.69±4.24, respectively. In terms of knowledge, only 26.8% had heard the term "ASPs" and knew what it was. Most incorrect answers appeared to the treatment of infection caused by MDR bacteria including ESBL-producing E-coli (27.8%) and carbapenemresistant K. pneumoniae (30.8%), as well as the atypical bacteria (45.5%). Approximately, 50% and 71.7% said they had received no specific training in the fields of microbiological sampling methods and the appropriate time to prescribe antibiotics, respectively. Surprisingly, regarding practice, 81.8% of the respondents stated that antibiotics are used to treat flu or the common cold. Conclusions: Residents considered their training on important issues including ASPs, MDR bacteria and the spectrum of antibiotics insufficient. This result highlights the need for targeted training interventions about antibiotic prescription in the curriculum at the university with more emphasis on ASPs to limit the development of resistance.